IMPLICATIONS OF OBSTRUCTIVE SLEEP APNEA IN CHILDREN WITH OBESITY - Lorena Mihaela Manole; Daniela Carmen Rusu; Mădălina Andreea Donos; Laura Otilia Boca; Otilia Elena Frăsinariu; Laura Mihaela Trandafir (Romanian Society of Oral Rehabilitation, 2022)
Obstructive sleep apnea is a chronic and severe breathing-related disorder, caused by adeno-tonsillar hypertrophy and has major impact in children. Obesity is a signifiant risk factor in the pathogenesis of this disease through alteration of the anatomy and the collapsibility of airways which alters the respiratory control. The aim of this systematic review was to identify the oral implications in pediatric population with obstructive sleep apnea and to highlight the importance of healthy approaches and prevent the negative effects on general health in later childhood and adulthood. Materials and method: In this review was made a literature search of articles published in international indexed databases PubMed, Medline and Web of Science. We analized only original research articles in English using the following search terms: sleep apnea, obesity, pediatric, adenoid hypertrophy. Results: The articles were studied and analyzed to be according to the subject. The clinical presentation of a child with obstructive sleep apnea is quite representative and has elements which can be classified as symptoms and physical findings. Discussions: Obstructive sleep apnea syndrome in pediatric population is a complex condition associated with various risk factors and potential complications, which is influenced by genetic, environmental and lifestyle factors. Obesity represents one of the most important risk factor in obstructive sleep apnea syndrome in both adults and children. Pediatric patients with sleep apnea and obesity have numerous implications in neurobehavioral, cardiovascular and growth impairment. Studies showed that the underlying causes of this pathology is complex and the obesity is direct implicated as a principal risk factor. Conclusions: Obstructive sleep apnea in children and adolescents is a condition with a multi-factorial etiology. Obesity and obtructive sleep apnea syndrome represents actionable problems with increasing prevalence in our society. Whether approached individually or altogether, treatment of these problems can improve quality of life, ease associated psychological burden and have positive economic implications.